The initiatory journey: Brendan y Dante - Jaime-Ramírez, Helios (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
The aim of this paper is to develop, by means of a comparative study, the theme of the journey as a revelation of the sense of existence, as well as its correlation with historical reality. The texts referred to are Navigatio Sancti Brendani and Divina Comedia. The existing relationships between these two texts are analysed, both considering lhe space-time structure and the three stages on which a glohal Universal vision is based.